2014
DOI: 10.14503/thij-13-3359
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oversized Injectable Valves in Growing Children for Total Repair of Right Ventricular Outflow Tract Anomalies (Preliminary Results)

Abstract: B ecause congenital anomalies of the right side of the heart are often characterized by a wide spectrum of right ventricular outflow tract (RVOT) and pulmonary valve (PV) alterations, the RVOT and PV are frequently involved in pediatric cardiac surgery. Nevertheless, the PV remained neglected for a very long time; it has gained consideration only in recent years.The first surgical corrections involved ventricular septal defect (VSD) closure and RVOT enlargement with a simple transannular patch, without attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These obstacles for an interventional valve-in-valve procedure were the reason for the need for surgery in three patients. Deorsola and Abbruzzese [6] found this prosthesis very helpful in young children. From our experience, we cannot support their judgement.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These obstacles for an interventional valve-in-valve procedure were the reason for the need for surgery in three patients. Deorsola and Abbruzzese [6] found this prosthesis very helpful in young children. From our experience, we cannot support their judgement.…”
Section: Discussionmentioning
confidence: 95%
“…The No-React® Injectible valve was introduced as a modern surgical valve replacement for minimally invasive and even off-pump procedures [1][2][3][4][5][6]. The potential advantages were ease of implantation, favourable tissue constitution and a perfect landing zone for a percutaneous valve-in-valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports and small pilot studies have reported that IPVs are easy to implant and have satisfactory function 1–9. However, when the Injectable Valve Implantation Trial (INVITE) was designed, no randomised controlled trial (RCT) had been conducted to evaluate valve replacement with IPV.…”
Section: Introductionmentioning
confidence: 99%
“…However, pulmonary valve-preserving repair in patients with severe hypoplastic pulmonary valves remains challenging and controversial ( 5 , 6 ). Deorsola and colleagues proposed the preliminary results of an innovative procedure consisting in the implant of an injectable biological pulmonary valve, designed for right infundibular surgery in adults; in babies: the valves, shrunken to a smaller diameter, enable the implantation of a device wider than otherwise possible in young patients and once in the pulmonary position tends to expand to its original size following patient’s growth ( 7 ).…”
Section: Introductionmentioning
confidence: 99%